Effect of Photoperiod on Dry Matter Production and Mineral Uptake by Chir (Pinus roxburghii Sarg.) Seedlings - Bhatnagar, H. P.; Gupta, B. B. (Indian Forester, 1975)
Pot culture experiment was conducted with Chir (Pinus roxburghii) seedlings to study the effect of photoperiod on dry matter production and mineral uptake. Significant differences in the dry weights of seedlings have been recorded among the photoperiodic treatments. Long dry treatment of 18 hours is significantly superior to other treatments; the highest amount of dry matter was produced under this treatment. As regards mineral uptake direct correlation has been observed, both in root and shoot portions, with dry matter production.